Mineral processing design and operation an introduction - Gupta, A. (Elsevier, 2006)
Mineral Processing Design and Operations is expected to be of use to the design engineers engaged in the design and operation of mineral processing plants and including those process engineers who are engaged in flow-sheets development. Provides an orthodox statistical approach that helps in the understanding of the designing of unit processes. The subject of mineral processing has been treated on the basis of unit processes that are subsequently developed and integrated to form a complete strategy for mineral beneficiation. Unit processes of crushing, grinding, solidliquid separation, flotation are therefore described in some detail so that a student at graduate level and operators at plants will find this book useful. Mineral Processing Design and Operations describes the strategy of mathematical modeling as a tool for more effective controlling of operations, looking at both steady state and dynamic state models. * Containing 18 chapters that have several worked out examples to clarify process operations * Filling a gap in the market by providing up-to-date research on mineral processing * Describes alternative approaches to design calculation, using example calculations and problem exercises.